2020
DOI: 10.3390/jcm9082553
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Events in Dual Disorders: Prevalence and Clinical Characteristics

Abstract: Psychological trauma has been identified in substance use disorders (SUD) as a major etiological risk factor. However, detailed and systematic data about the prevalence and types of psychological trauma in dual disorders have been scarce to date. In this study, 150 inpatients were recruited and cross-sectionally screened on their substance use severity, psychological trauma symptoms, comorbidities, and clinical severity. One hundred patients fulfilled criteria for a dual disorder, while 50 patients were diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Likewise, 71.5% of the whole sample met the criteria for current PTSD, adding a further comorbidity in this complex population. These data are far higher than the prevalence data found in the general population, which range from 0.2% to 3.8% [ 53 ], and also higher than in mental disorders such as depression (48–49%) [ 54 ], bipolar disorder (4% to 40%) [ 55 ], or substance use disorder (20.67%) [ 56 ]. It is important to note that almost half of the sample ( n = 34) was selected for the administration of the EGEP-5, an event that occurred in childhood that was the most significant traumatic event in their lives.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, 71.5% of the whole sample met the criteria for current PTSD, adding a further comorbidity in this complex population. These data are far higher than the prevalence data found in the general population, which range from 0.2% to 3.8% [ 53 ], and also higher than in mental disorders such as depression (48–49%) [ 54 ], bipolar disorder (4% to 40%) [ 55 ], or substance use disorder (20.67%) [ 56 ]. It is important to note that almost half of the sample ( n = 34) was selected for the administration of the EGEP-5, an event that occurred in childhood that was the most significant traumatic event in their lives.…”
Section: Discussionmentioning
confidence: 94%
“…Brunault et al [11] observed that the existence of childhood trauma is more related to the clinical remission of patients with a diagnosis of alcohol-use disorder and post-traumatic stress disorder than the severity of both diagnoses. Along the same line is the contribution of Blanco et al [12], which points to childhood maltreatment as a predictor of both developing a DD and a more complex and severe clinical profile. In DD patients, the evaluation of traumatic events in childhood and integrating specific therapy into the treatment is an option for a better prognosis.…”
mentioning
confidence: 83%
“…The attention given for the high prevalence rates of physical abuse (47-65%), sexual abuse (36-37%), and post-traumatic stress disorder (PTSD) (30-34%) in patients with severe mental illness (SMI) is still growing (1)(2)(3). The need for adequate diagnostics and treatment is increasingly recognized because trauma and PTSD have a negative influence on the course of SMI, including an increased risk of poor physical health; addiction; problems with social, occupational, and community functioning; reduced quality of life; and criminalization (1,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%